Comparative Analysis of Indonesia-China High Speed Train and KTX Korea-France: A Sustainable Development for Locals or Reconfiguring Other Interests - Darynaufal Mulyaman; Kanya Damarçanti (Parahyangan Center for International Studies, 2021)
This study undermines a recent development of joint-cooperation between Indonesia and China regarding high-speed railway and its supporting constructions. New dedicated railway, train technology, and Transit Oriented Development (TOD) are part of the initial project, which planned concurrently along the projected area. All of these new railway and TODs are new and distant from already built residences and business centers. These study breakdowns how the Indonesia-China High Speed Train project were initiated and explaining vital factors that surrounds it. Reflecting on how Korea and France dealt with KTX (Korean Train Express) project, the TODs, railways, and train technology compare to Indonesia-China High Speed Train project, Indonesia-China project appears not sustainable and driven by other political and economical will.